Permeability Effect of Green Roof Drainage Board - Pelin Sertyeşilışık; Tayfun Uygunoğlu (Doğal Afetler ve Çevre Dergisi)
Populations in cities result in the building of housing, transportation, and industry, which might cause to alter the permeable surfaces to impermeable surfaces. However, permeable terrain is essential for stormwater management. One of the environmentally friendly ways to collect rainwater is to install green roofs, and there are examples of this all over the world. Using the green roof system helps lessen flash floods and sewage floods in cities, which are today's most significant issues. Due to the fact that the rain water can be collected and used efficiently via green roof systems the effects of the form of the bottom layer of the extensive green roof on the output flow were investigated using both with and without drainage layer systems in this study. Rainfall-runoff events were observed by a water flow sensor and a green roof setup with surface slopes of 3, 6, and 12% were constructed as a model. According to the results, surface flow from the drainage board at all slopes is delayed by 68-81% compared to the empty surface. In addition, it has been noted that the surface permeability coefficient ranges between 0.5-0.7 and has taken values lower than the empty surface when there is a drainage board at the base of the green roof. As a result, it has been seen that laying the drainage board in green roof systems can be effective in reducing the intensity of precipitation in cities. In the case of using bubble sheets in green roof systems, a range for the C coefficient to be used in precipitation-flow calculations for different slopes has been revealed. The outputs of this study can be used to manage the flood disasters that may occur in cities due to the increased rainfall intensity due to climate change and to reduce the material and moral damage that may occur.